The overall pathological status of the left hippocampus determines preoperative verbal memory performance in left mesial temporal lobe epilepsy - Witt, Juri-Alexander; Coras, Roland; Schramm, Johannes; Becker, Albert J.; Elger, Christian E.; Blümcke, Ingmar; Helmstaedter, Christoph (Hippocampus, 2014)
Studies on hippocampal cell loss in epilepsy have produced diverging evidence as to which subfields are specifically related to memory. This may be due to rather small and often heterogeneous samples, or to different memory measures. Therefore, the current study examined hippocampal cell densities and memory in a large sample of patients with solely mesial temporal lobe epilepsy (mTLE), employing measures with proven sensitivity to mesiotemporal pathology. In 104 patients who had undergone epilepsy surgery for mTLE, we evaluated the role of segmental hippocampal cell loss and its underlying factor structure with regard to presurgical verbal and figural memory while controlling for side-of-surgery and hemispheric dominance. First of all, patients showed material-specific memory impairment concordant with the lateralization of epilepsy. Factor analysis of segmental cell loss revealed a single factor reflecting the overall integrity of the hippocampus. The overall pathological status of the left hippocampus correlated with verbal memory parameters (r = 0.33-0.34, P < 0.05), especially when controlling for atypical hemispheric dominance (r = 0.50-0.57, P < 0.01), and explained up to 33% of the observed variance. Further analyses revealed no superior role of a single subfield or cell loss pattern for memory performance. No systematic relations between neuronal cell densities of the right hippocampus and memory function were found, nor did left or right hippocampal pathology explain figural memory parameters. The results suggest that the overall pathological status of the left hippocampus - rather than a specific subfield pathology - is predictive for verbal memory in mTLE. The finding that figural memory parameters, although sensitive to right mTLE, were not related to neuronal cell densities of the right hippocampus, puts the left/right hippocampus verbal/nonverbal memory dichotomy into perspective. © 2014 Wiley Periodicals, Inc.
EVALuna2:7228